Free will and consciousness how might they work? - Baumeister, Roy F.; Mele, Alfred R., 1951-; Vohs, Kathleen D. (New York ; Oxford : Oxford University Press, 2010)
This volume is aimed at readers who wish to move beyond debates about the existence of free will & the efficacy of consciousness & closer to appreciating how free will & consciousness might operate. It draws from philosophy & psychology, the two fields that have grappled most fundamentally with these issues.
Includes index.
Description based on online resource; title from home page (viewed Sept. 7, 2010).
Keywords: Free will and determinism; Consciousness